2019
DOI: 10.1016/j.dadm.2019.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Peak width of skeletonized mean diffusivity and its association with age‐related cognitive alterations and vascular risk factors

Abstract: Introduction Only two studies investigated the associations between peak width of skeletonized mean diffusivity (PSMD) and age‐related cognitive alterations, whereas none of the studies investigated the association with vascular risk factors. Methods We evaluated 801 stroke‐ and dementia‐free elderlies with baseline and 3‐year follow‐up assessments. Regression analyses were used to assess the association between age‐related cognitive functions and PSMD. Simple mediation models were used to study the mediation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 29 publications
(33 reference statements)
2
34
3
Order By: Relevance
“…[ 6 , 17 ] Interestingly, our group further found that the expression changes of AD susceptibility genes appear especially prominent at the capillary endothelium, suggesting a possible etiological role of capillary endothelial dysfunction in AD. [ 4 ]…”
Section: Pathology and Pathophysiologymentioning
confidence: 99%
See 3 more Smart Citations
“…[ 6 , 17 ] Interestingly, our group further found that the expression changes of AD susceptibility genes appear especially prominent at the capillary endothelium, suggesting a possible etiological role of capillary endothelial dysfunction in AD. [ 4 ]…”
Section: Pathology and Pathophysiologymentioning
confidence: 99%
“…There are certain brain changes that are associated with CSVD but may not be captured by pathological studies or conventional MRI sequences or CT, these include diffusion tensor imaging (DTI) (fractional anisotropy, mean diffusivity, peak weak of skeletonized mean diffusivity) and functional MRI, which reflect white matter microstructural changes and brain network connectivity changes, respectively. [ 4 , 34 ] In addition, the BBB leakage and neuroinflammation can also be captured by dynamic contrast-enhanced MRI [ 35 ] and translocator protein positron emission tomography (PET) imaging, respectively. [ 36 ]…”
Section: In Vivo Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of note, this review focused on the CSVD imaging features that are visible on conventional structural MRI as detailed in STRIVE criteria. Although, some CSVD features from advanced MRI modalities [ 2 ] (eg, diffusion tensor imaging) have been validated for their robustness for clinical studies [ 3 , 4 ] or even as secondary outcomes in clinical trials [ 5 ] (eg, peak width of skeletonized mean diffusivity that could sensitively capture CSVD progression), they would not be discussed in the following sections.…”
Section: Introductionmentioning
confidence: 99%